PERAN MULTIMEDIA INTERAKTIF DALAM MENGATASI KESULITAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN ISLAM (PAI) SISWA KELAS X DI SMA NEGERI 2 SENTAJO RAYA - Rohmad Wandy Satriawan; Andrizal Andrizal; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2020)
Learning media have a variety of forms, from simple to complex media. The development of technology and information also contributed to the increasingly rich learning media that can be utilized by the teacher. A complicated problem often faced by teachers is the presence of students who have learning problems. Or often referred to as learning difficulties. Recently emerged the latest learning media that can overcome these problems, namely Interactive Multimedia. In observations made by researchers at SMA Negeri 2 Sentajo Raya, the use of media was not optimal. So that it will be able toobstruct the learning objectives themselves. See the conditions in the field. Researchers are interested in studying these problems with the aim of being able to find out how the role of interactive multimedia in overcoming student learning difficulties in PAIsubjects. The author uses data collection techniques such as observation, interviews and documentation. The type of this research uses the type of field research (field research) that is descriptive qualitative. The steps of this research consist of determiningthe focus of the study, determining the settings and subjects of research and data collection, data processing and data analysis. Data analysis techniques use data reduction (Data Reduction), data presentation (Data Display) and conclusions. Based on the results of the study found that Interactive Multimedia plays a role in overcoming studentlearning difficulties. Because interactive multimedia includes various combinations of text, graphics, sound, animation and video delivered using tools such as laptops, computers, infocus, speakers, wifi and others. As well as this interactive multimedia cangenerate student action to communicate both ways between teacher and student, as well as students with the media.